RESPONS TINDAK LANJUT REKOMENDASI AUDIT MATERNAL DI KABUPATEN BREBES DAN KABUPATEN BANYUMAS - Dessyana Iriani; Eugenius Phyowai Ganap; Dwi Handono Sulistyo (Journal of Health Service Management, 2021)
Background: The number of cases of maternal deaths in several districts is still high and has increased as in Brebes and Banyumas districts. The Maternal Perinatal Audit Policy in the District / City as an effort to reduce the number of maternal deaths is felt to be unsuccessful. In addition, the extent to which policy makers and implementers respond to or follow up on the results of maternal audit recommendations is still a big question. Objective: To explore the responses and factors that influence the implementation of follow-up maternal audits recommendations in Brebes and Banyumas Districts. Methods: This study used a qualitative design with a case study research design. Data collection techniques through document review, in-depth interviews and focus group discussions with a total of 14 informants. Results: The immediate response to the follow-up to the maternal audit in Brebes Regency was adequate and in Banyumas District good. Planned responses in both districts were not analyzed in this study because terms of reference for activities is not reviewed. Based on the characteristics of the problems the Brebes Regency is difficult to control because there are still many problems in the field and Banyumas Regency is easy to control. Based on the Policy Characteristics of the two districts included in the good category and based on the environment the Brebes Regency has not supported and the Banyumas Regency environment supports the implementation of the follow-up to the maternal audit recommendations. Conclusion: The response of the regencies is very dependent on leadership to make decisions immediately. The immediate response to the follow-up of the maternal audit in Brebes Regency was sufficient and in Banyumas District was good. It is recommended that the District Health Offices need to make a follow-up SOP on recommendations to the implementation of monitoring and evaluation by adding a reward and punishment system and Brebes Regency should accelerate the process of adding PONEK Hospitals and pay more attention to the principles of response in MDSR.